Contribution of Teacher Social Competency to Characteristic Education of Elementary Students - Ummah, Inayatul; Udin, Tamsik (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
This study aims to analyze and determine the contribution of teacher social competence to the characteristic education of elementary school students. The approach used in this study was a literature review. This study discussed the social competence of the teacher in applying at elementary school for support characteristic education in elementary school. The social competence of teachers is a part of the way to communicate and socialize effectively with students, fellow teachers, parents of students, and the surrounding community. Teacher needs social competence because they share their knowledge and also transmit character to the students. Character education in Indonesia has again become a new trend due to changes in the independent curriculum. Therefore teachers should learn how to clearly communicate and include characteristic education in every lesson.